(3GdeSGFd GdRGgQI hGdCLhHI GdHGgQIs - (3GHf XgjQI , LeGd GdOjf CHh MGeO,J (B816 (3g` s
(3ChdgG (B:s
(3CeG HYO abO hQOJ Ydi gPg GdeSGFd GdeajOI ef HdGO RgQGf ef Gdabjg GdaGVd GdUGdM CHj GSMb EHQGgje Hf Ydi GdRgQGfi GdeYQha HGHf YGdjg s
(3BNQgG (B:s
(3hjMJGW LgOg hdG jJhba HPdc Ydi eG bQCg hGddg JYGdi CYde hHg GdJhajb SHMGfg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B221s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3Gdabg GdTGaYjs